2004
DOI: 10.3406/ccgg.2004.858
|View full text |Cite
|
Sign up to set email alerts
|

The lex Valeria and Sulla’s empowerment as dictator (82-79 BCE)

Abstract: In November 82 BCE, the victorious proconsul L. Cornelius Sulla (cos. 88) revived the dictatorship to restore law and order in the battered Republic. L. Valerius Flaccus (cos. 100), then princeps senatus, was appointed interrex by the patrician patres. After obtaining the necessary clearances from the Senate and the augural college, Flaccus passed a law ordering him to appoint Sulla to an unprecedented dictatura legibus scribundis et rei publicae constituendae, and himself to the office of magister equitum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…infra n. 91. For the suggestion that the Valerian Law probably invested Sulla with (certain components of) the potestas censoria in his capacity of dictator, see Vervaet (2004) 47. 65 The wording in 1.118: ἀφικόμενος δὲ καὶ τὰ τῶν ὑπάτων δύο προσέλαβε suggests that Appian believed the consuls to have commanded one legion each.…”
Section: The State Of the Questionmentioning
confidence: 99%
“…infra n. 91. For the suggestion that the Valerian Law probably invested Sulla with (certain components of) the potestas censoria in his capacity of dictator, see Vervaet (2004) 47. 65 The wording in 1.118: ἀφικόμενος δὲ καὶ τὰ τῶν ὑπάτων δύο προσέλαβε suggests that Appian believed the consuls to have commanded one legion each.…”
Section: The State Of the Questionmentioning
confidence: 99%
“…51 Frederik Vervaet argues that the first interrex was perfectly qualified to preside over the assembly, but that it was not customary for him to do so because of religious scruples in maintaining optimal public auspices. 52 On the basis of the fact that the auspices could only be consulted by individual persons, Jerzy Linderski has suggested that the first interrex was actually selected by lot. The suggestion, if there were any evidence for the lots, would explain why it was only the second interrex who was appointed auspicato, or why his successors were qualified to convene the electoral assembly.…”
Section: From the Board Of Ten To Two Interregesmentioning
confidence: 99%
“…On placards: Östenberg, 2009c. 23 On Sulla and justification, see : Vervaet, 2004. On the triumvirs' use of Sulla as a model, see : Vervaet, 2004: esp.…”
Section: Pompeius's African and Spanish Triumphsmentioning
confidence: 99%